2015
DOI: 10.1159/000376594
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia Is Now Included in the NCCN Clinical Practice Guidelines for Breast Cancer Recurrences: An Analysis of Existing Data

Abstract: Background: Hyperthermia has been included in the 2013 National Comprehensive Cancer Network (NCCN) guidelines as an option for the treatment of breast recurrences. The purpose of this article is to demonstrate the important role of hyperthermia as a therapeutic modality by presenting clinical trials on this subject carried out in the last decades. Materials and Methods: All relevant trials published since 1987 were retrieved from Medline and reviewed. Results: Results show that the addition of hyperthermia to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The measured SAR values of the F‐MH are 371 (150 Oe) and 856 (220 Oe), respectively, almost 4.5‐ and 7.5‐fold greater than that of S‐MH, indicating the superiority of F‐MH with respect to induction heat (Figure c). Moreover, repeated or multiple hyperthermia treatments are normally adopted instead of one single treatment in clinical oncology 18c,30. Therefore, the temperature increase cycle was also measured, and the results have been presented in Figure d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured SAR values of the F‐MH are 371 (150 Oe) and 856 (220 Oe), respectively, almost 4.5‐ and 7.5‐fold greater than that of S‐MH, indicating the superiority of F‐MH with respect to induction heat (Figure c). Moreover, repeated or multiple hyperthermia treatments are normally adopted instead of one single treatment in clinical oncology 18c,30. Therefore, the temperature increase cycle was also measured, and the results have been presented in Figure d.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the intrinsic or acquired multidrug resistance resulting from individual variations is a major reason for the failure of these postoperative adjuvant therapeutic approaches . Recent advances in cancer medicine have revealed that physical hyperthermia combined with radiotherapy and/or chemotherapy can yield an optimized synergistic anticancer outcome 15c,18. In this context, the development of FVIO‐incorporated hydrogel with optimally adaptive functions ( Scheme ) and which can achieve efficient synergistic thermo‐chemotherapy may offer an alternative approach to address unmet clinical needs 1a,19…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, local control during lifetime is always the main therapeutic objective due to the extreme suffering caused by a visible disease requiring extensive care procedures and that may lead to social isolation. Recent reviews of randomised studies and retrospective analyses confirm the additional benefit of combined RT/HT for pre-irradiated recurrent breast cancer [21][22][23][24]. Inflammatory disease is reported to have a worse prognosis and significantly lower CR-rates [25,26].…”
Section: Discussionmentioning
confidence: 96%
“…BC with invasive lobular carcinoma (ILC) frequently affects bones, retroperitoneum, peritoneum, gynaecological organs, and gastrointestinal (GI) tract [2][3]. The ve-year survival of BC has been increasing but the treatment of recurrent BC is a challenge [4][5]. Especially peritoneal metastasis from BC is a poorly de ned entity [6].…”
Section: Introductionmentioning
confidence: 99%